Hippo/Mst signaling coordinates cellular quiescence with terminal maturation in iNKT cell development and fate decisions - Raynor, Jana L. (J Exp Med, 2020)
Invariant natural killer T (iNKT) cells acquire effector functions during development by mechanisms that remain poorly understood. Here, we show that the Hippo kinases Mst1 and Mst2 act as molecular rheostats for the terminal maturation and effector differentiation programs of iNKT cells. Loss of Mst1 alone or together with Mst2 impedes iNKT cell development, associated with defective IL-15–dependent cell survival. Mechanistically, Mst1 enforces iNKT cellular and transcriptional quiescence associated with maturation and commitment to iNKT1 cells by suppressing proliferation and Opa1-related mitochondrial metabolism that are dynamically regulated during iNKT cell development. Furthermore, Mst1 shapes the reciprocal fate decisions between iNKT1 and iNKT17 effector cells, which respectively depend upon mitochondrial dynamics and ICOS–mTORC2 signaling. Collectively, these findings establish Mst1 as a crucial regulator of mitochondrial homeostasis and quiescence in iNKT cell development and effector lineage differentiation and highlight that establishment of quiescence programs underlies iNKT cell development and effector maturation.